Seismic velocity structure of the crust and uppermost mantle beneath the Tien Shan and its adjacent areas - Zhang, Shengzhong; Zhang, Bing; Zhou, Ming; Ouyang, Longbin (Frontiers in Earth Science, 2023)
The Tien Shan and its adjacent areas have been a prime place to understand the process of continental collision, the mechanism of mountain building and the interaction of tectonic blocks. In this study, we collect seismic data recorded by 74 broad-band stations from the China Provincial Digital Seismic Networks and the Regional Kyrgyzstan and Kazakhstan Networks between January, 2007 and September, 2009. A joint inversion technique that combines three types of datasets (receiver functions, phase velocities of Rayleigh wave measured from both ambient noise and teleseismic earthquake data) is applied to image the crustal and upper mantle structure beneath the Tien Shan and its adjacent areas. The average crustal thickness in the study area is about 50 km, however, the Moho depth extends to ~70 km beneath the Kokshaal Range near the southwestern Tien Shan. Our velocity models show a good correlation with subsurface geological features at shallow depths: low velocities are predominantly observed beneath the basins due to thick sedimentary layer, whereas high velocities are mainly distributed beneath the mountain ranges due to crystalline basement rocks. In the upper mantle a low velocity zone is obviously observed beneath the western Tien Shan. Both the crust thickness and S wave velocity structure of the Tien Shan and its adjacent regions display obvious horizontal and vertical heterogeneities from west to east, which suggests that the far-field effects of the collision between Eurasian plate and Indian plate plays an important role in the tectonic activity of the Tien Shan. The apparent velocity heterogeneities beneath the northern Tarim Basin may indicate that the Tarim Basin may have been eroded and damaged by upwelling hot materials from the upper mantle.